Nocardia Cyriacigeorgica Bacteremia in an Immunocompetent Patient - Rafey, Abdur; Khan, Aamir; Abbas, Salma Muhammad (Infectious Diseases Journal of Pakistan, 2022)
Nocardia is a gram-positive rod with appearance of branching hyphae. Nocardia asteroides complex was responsible for most infections; now Nocardia cyriacigeorgica is more frequently identified. It usually is an opportunistic pathogen with the majority of infections occurring in patients with immunosuppressive conditions. Patients with depressed cellmediated immunity especially are at high risk for infection. However, it can cause disease in immunocompetent patients.4 Nocardia is rare and has mortality of 40%. We are writing this case report to address an unusual case of Nocardia cyriacigeorgica bacteremia in a young female without any risk factors. It will help for better understanding of Nocardia infection in healthy persons and improvement of patient care.